Comparing the effects of chlorhexidine solution with or without toothbrushing on the development of ventilator-associated pneumonia among patients in ICUs: a single-blind, randomized controlled clinical trial - Gholamhossein Falahinia; Maryam Razeh; Mahnaz Khatiban; Mahbobeh Rashidi; Alireza Soltanian (Tehran University of Medical Sciences, 2016)
Background & Aim: Poor oral care for the ventilated patients in intensive care units (ICU) can result in the accumulation of pathogens and respiratory infections. In this regard, in addition to the chemical methods, a mechanical method has been recommended to be added. However, concerning its effect on pneumonia, different findings have been reported. Therefore, this study was conducted to compare the effects of chlorhexidine solution with or without toothbrushing on the development of ventilator-associated pneumonia among patients in ICUs. Methods & Materials: This was a single-blind, randomized controlled clinical trial conducted in two selected hospitals of Ahvaz city in 2014. A convenience sample of 68 ventilated patients was randomly allocated to the toothbrush group (34 patients) or the gauze swab group (34 patients) using R software. Both groups received 0.2% Chlorhexidine solution. The intervention was performed in both groups for 3 minutes twice a day for five days. At the end of the fifth day, the development of pneumonia was assessed using the Clinical Pulmonary Infection Score (CPIS). Data were analyzed by Chi-square and t-independent test through SPSS v.16. Results: The two groups were similar for age, sex, cause of admission, level of consciousness, medication and tobacco use. The majority of patients (58.8%) were diagnosed with pneumonia (Group A: 55.9% and Group B: 61.8%). The Chi-square test showed no significant difference between the two groups for the development of pneumonia (P>0.05). Conclusion: The use of Chlorhexidine solution with toothbrushing compared to using Chlorhexidine with swab could not reduce the development of pneumonia. However, due to its importance, further research is needed in this regard.